The Influence of Financial Risk, Cash Flow, and Capital Structure on the Financial Performance of Manufacturing Companies on the Indonesia Stock Exchange - Selomita Dina Pransisca; Cahyo Pramono; Dr. Pipit Buana Sari (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
This study aims to analyze the effect of financial risk, cash flow, and capital structure on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange. The independent variables include financial risk proxied by working capital, cash flow proxied by retained earnings and sales, and capital structure proxied by earnings before interest and taxes (EBIT) and market value of equity. The dependent variable is financial performance measured using Return on Assets (ROA) and Return on Equity (ROE). The method used is a quantitative approach with multiple linear regression analysis. The data used are secondary data obtained from financial statements of manufacturing companies. The results show that financial risk, cash flow, and capital structure partially and simultaneously have a positive and significant effect on financial performance. These findings indicate that effective financial management through risk control, cash flow optimization, and appropriate capital structure decisions can improve financial performance.